The Role of Civil Bureaucracy—Facilitative or Regressive? Perspectives from Pakistan - Taj, Aamer (The Journal of Humanities & Social Sciences, 2022)
This paper explores some of the theoretical limitations of classical theory of bureaucracy. It also analyses Pakistani bureaucracy’s organisational composition and behaviour which reveals that the Pakistan’s civil administrative structure is incongruent with the principles indoctrinated in the classical theory of bureaucracy postulated by Max Webber. When the civil bureaucracy of a state trespasses into the domain of other institutions including the political ones, the very character of the civil administration becomes politicised and this phenomenon is evident in the case of Pakistan. Likewise, the civil administrative institutions are routinely pressurised for manipulating and twisting their rule-bound operating procedures in accordance with the vested interests of politicians. This makes the politicisation of administration inevitable and the concept of ‘legal rational authority’, a highly idealised principle. The organisational and institutional analysis of Pakistan’s civil bureaucracy illustrates that it is a poor materialisation of the classical model of bureaucracy mainly because this system of administration was inherited from the epoch of colonial rule and as such it was never a manifestation of the theory of bureaucracy in the first place.